1997
DOI: 10.1002/(sici)1520-6807(199701)34:1<51::aid-pits6>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Predicting teacher referrals of emotionally disturbed children

Abstract: The degree to which teachers' perceptions of a student can be distorted by characteristics indigenous to teachers, as well as students, were investigated to determine whether teachers would initiate a referral for special education. Sixty‐five teachers volunteered for participation. Twenty‐seven of them were experienced, having had their own classrooms in a public school. Thirty‐eight were preservice student teachers who had not yet had their own classrooms. Teachers were evaluated to have had either an intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
(28 reference statements)
2
14
0
Order By: Relevance
“…Although the scope of the findings may be limited to similar samples, they indicate that personality and stress should not be underestimated when studying the determinants of teachers' appraisals. In fact, these findings raise questions regarding the accuracy of teacher perceptions of their students given that these are filtered through a number of parameters that are indigenous or contextual to the teacher (Schwartz et al, 1997). Further research should address the interaction between teachers' stress and personality in the same sample, and replicate the findings in other cultural contexts.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although the scope of the findings may be limited to similar samples, they indicate that personality and stress should not be underestimated when studying the determinants of teachers' appraisals. In fact, these findings raise questions regarding the accuracy of teacher perceptions of their students given that these are filtered through a number of parameters that are indigenous or contextual to the teacher (Schwartz et al, 1997). Further research should address the interaction between teachers' stress and personality in the same sample, and replicate the findings in other cultural contexts.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, experienced teachers were found to be more tolerant of student undesirable behaviors, a finding that as Borg (1998) suggested may be attributed to the fact that after the difficult initial years, teachers come to realize the relative mild nature of problem classroom behaviors and form their attitudes accordingly. Teaching experience also plays a prime role in teachers' decision for special education referrals, as Schwartz, Wolfe, and Cassar (1997) found that teacher personality predicted the decisions of preservice, but not in-service, teachers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, it is noted that teachers' perceptions of a student may be distorted by characteristics of teachers themselves, such as their own locus of control, self-esteem and extent of teaching experience (Schwartz, Wolfe, & Cassar, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…According to Schwartz, Wolfe, & Cassar, (1997) inexperienced teachers appear to be sensitive to the issue of classroom control, especially when working with ED students. Further, their opportunity for experience is further curtailed as the teachers attempt to meet the challenges provided by the student.…”
Section: Educational Leadershipmentioning
confidence: 99%